2022
DOI: 10.53941/ijndi0101006
|View full text |Cite
|
Sign up to set email alerts
|

From Emotion AI to Cognitive AI

Abstract: Survey/review study From Emotion AI to Cognitive AI Guoying Zhao *, Yante Li , and Qianru Xu University of Oulu, Pentti Kaiteran Katu 1, Linnanmaa 90570, Finland * Correspondence: guoying.zhao@oulu.fi     Received: 22 September 2022 Accepted: 28 November 2022 Published: 22 December 2022   Abstract: Cognitive computing is recognized as the next era of computing. In order to make hardware and software systems more human-like, emotion artificial intelligence (AI) and cognitive AI which simulate human intellig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 67 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Distinguishing different genders of virtual hands or designing personalized virtual hands for VR applications may lead to a deeper investigation of users’ embodied cognition in future. Furthermore, it is suggested that implementing cognitive artificial intelligence in VR systems can make them capable of analyzing and making decisions like human users (Zhao et al , 2022), which can help import the cognition capability to systems for better interaction between people and VR.…”
Section: Discussionmentioning
confidence: 99%
“…Distinguishing different genders of virtual hands or designing personalized virtual hands for VR applications may lead to a deeper investigation of users’ embodied cognition in future. Furthermore, it is suggested that implementing cognitive artificial intelligence in VR systems can make them capable of analyzing and making decisions like human users (Zhao et al , 2022), which can help import the cognition capability to systems for better interaction between people and VR.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, based on the findings of this study, task performance has an impact on users’ feeling of control, and scholars have attempted to enhance work quality by improving task efficiency in CAD as a way to show better creative idea generation in the design process (Veisz et al , 2012). It is also proposed that introducing cognitive artificial intelligence to the system can allow the system itself to analyze and make decisions like users (Zhao et al , 2022), which can bring cognition capability to the system for the enhanced user experience. On the other hand, we examined changes in SoA with different translation modes and 2D interface types as measured by EEG data; additionally, EEG has been shown to provide insights into designers’ creative ideas (Liu et al , 2018; Jia and Zeng, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DCP-A can be extended into multi-task pruning. In the future, we will 1) consider more different guidance mechanisms with layer information [32,46,47,49,56,57,66], 2) introduce control strategies to enhance the model robustness [3,27,33,50,51,58], and 3) extend our approach to other complicated multi-task learning problems [1,23,34,59,65,67].…”
Section: Discussionmentioning
confidence: 99%